Cultural Erosion: Post-Colonial Discourse in Achebe's Things Fall Apart - Chapagaee, Rajendra Prasad (International Journal of Humanities, Education, and Social Sciences, 2024)
The purpose of this research is to examine the erosion of cultural identity of Igbo society as a result of British colonization. It also looks at the colonial hegemony enforced by institutions of the church, judiciary, medical system, and education in Igbo society. The peaceful Igbo village descends into chaos as the protagonist's son disobeys his father and mocks the idea of brotherhood by converting himself into Christianity. The impact of colonialism and the supremacy of European culture destroys the social harmony of Igbo society. As a result, despite the struggle and sacrifice of true lover of original culture, the rich cultural legacy continues to collapse. A post-colonial social narrative raises questions to the aboriginal Igbo culture that was originally shaped by a variety of cultural ethos. The community experiences a significant transformation while the true followers original culture struggle with the shifting dynamics of relationships. The traditional lifestyle of the Igbo people is disrupted and challenged by European civilization. As they resist the changes imposed by the colonizers, the indigenous people's identity changes.